Comparison of efficacy of large tissue bites versus small tissue bites for midline abdominal wound closure - Mustaqrasool, Tappa Mahammad; Dikshit, Bharat; Phalgune, Deepak (International Surgery Journal, 2020)
Background: Incisional hernia is common complication after median laparotomy, with reported incidence varying between 2% and 20%. For prevention of incisional hernia, many clinical trials and meta-analyses have demonstrated that mass closure technique with simple running suture is good option to close midline incision. An attempt was made in this study to compare efficacy of large tissue bites vs small tissue bites for midline abdominal wound closure. Methods: Three hundred thirty patients admitted for midline laparotomy were randomized into Group A, and Group B. Group A, and Group B patients underwent abdominal closure by small bites technique, and large bites technique respectively. Patients were followed at 7th postoperative day, 1 month, 6 months, and 12 months. Primary outcome measures were incidence of incisional hernia, incidence of postoperative complications like post-operative pain, surgical site infections, wound dehiscence whereas, secondary outcome measure was fascial closure time. Inter-group comparison of categorical, and continuous variables was done using Chi-square test/Fisher’s exact test and unpaired ‘t’ test respectively. Results: Incidence of incisional hernia was significantly higher in large bites suture technique compared to small bites suture technique at 12 months follow up. Mean time required for fascial closure time was significantly higher in small bite group compared to large bite group. There was no statistically significant difference in postoperative pain, surgical site infections, and wound dehiscence among the two groups. Conclusions: The rate of incisional hernia was lower in small bites technique compared with large bites technique in midline abdominal incisions.